Transformasi Pesisir Jakarta: Kajian Komprehensif Giant Sea Wall untuk Keberlanjutan Sosial, Ekonomi, dan Ekologis - Agnesia Putri; Benny Yulius Richardo; Muhammad Zid; Cahyadi Setiawan; Ananto Kusuma Seta (Syntax Corporation Indonesia, 2025)
Jakarta faces a serious flood threat due to a combination of sea level rise, land subversion due to groundwater exploitation, and extreme rainfall. The Giant Sea Wall project is proposed as a solution to reduce annual economic losses of Rp 2.1 trillion, while protecting the city from flash floods and river floods, as well as supporting the development of coastal business and tourism areas. However, this project is faced with major challenges, such as funding needs that require innovation in the form of Green Financing and public-private partnerships, social resistance due to lack of community involvement, as well as ecological impacts such as the loss of mangrove habitat and disruption of sedimentation patterns. Global studies, such as Delta Works in the Netherlands, highlight the importance of ecosystem-based approaches and integrated design to ensure sustainability. The success of this project depends on the integration of mangrove restoration, the use of advanced technology, inclusive policies, and the active involvement of local communities to ensure equitable socio-economic impact as well as long-term sustainability.